2013
DOI: 10.1186/1477-7819-11-257
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic and clinicopathological patterns of esophageal cancer in Tanzania: experiences from two tertiary health institutions

Abstract: BackgroundEsophageal cancer is one of the most serious gastrointestinal cancer worldwide, owing to its rapid development and fatal prognoses in most cases. There is a paucity of published data regarding esophageal cancer in Tanzania and the study area in particular. This study was conducted to describe the endoscopic and clinicopathological patterns of esophageal cancer in this part of the world. The study provides baseline local data for future comparison.MethodsThis was a retrospective study of histologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 19 publications
(44 reference statements)
12
29
0
Order By: Relevance
“…The male predominance demonstrated by Mabula D Mchembe et al 5 in their study was in keeping with previous observation reported in a study performed elsewhere. However, equal gender distribution was reported in previous studies from Nigeria and Kenya.…”
Section: Discussionsupporting
confidence: 92%
“…The male predominance demonstrated by Mabula D Mchembe et al 5 in their study was in keeping with previous observation reported in a study performed elsewhere. However, equal gender distribution was reported in previous studies from Nigeria and Kenya.…”
Section: Discussionsupporting
confidence: 92%
“…The country has the goal of establishing more cancer centers in the future to avoid patients missing treatment. Finally, missing data was another limitation for this study [25,26] . HIV status is not commonly recorded for EC patients in Tanzania, as they receive the same treatment regardless of HIV condition.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Study done by Mchembe MD et al observed that grade IV dysphagia (43%) was most common at the time of presentation followed by least common grade II dysphagia (4.6%) that was dissimilar to present study. 10 Histopathological examination in our study revealed that most patients 92.50% had SCC and minimum patients 7.50% had adenocarcinoma and same was observed by Multimodality treatment and survival of patients was seen for carcinoma oesophagus, neoadjuvant therapy which was followed by surgery, it was found that in present study perioperative morbidity and mortality is higher after neoadjuvant chemotherapy and radiotherapy and as observed by Keditsu KK et al 12 MRC studies showed benefit with neoadjuvant chemotherapy and Sjoquist KM et al in meta-analysis found that definite survival benefit with preoperative chemotherapy in locally advanced oesophageal cancers. 13,14 The metaanalysis conducted by Arnott et al reported a poor benefit rate with preoperative radiotherapy alone.…”
Section: Discussionmentioning
confidence: 99%